PROX1 TRANSCRIPTION FACTOR AS A MARKER FOR VASCULAR TUMORS – EVALUATION OF 314 VASCULAR ENDOTHELIAL AND 1086 NONVASCULAR TUMORS - Miettinen, Markku (2012)
Prox1, a transcription factor important in regulation and maintenance of lymphatic endothelial phenotype, is consistently expressed in lymphangiomas and Kaposi sarcoma and has also been reported in Kaposiform hemangioendothelioma. However, information on its distribution of vascular tumors, such as angiosarcoma, is limited. In this study we examined selected normal tissues and 314 vascular endothelial and 1086 non-vascular tumors in order to get insight into biology of these tumors and on potential diagnostic use of Prox1 as an immunohistochemical marker. In adult tissues, Prox1 was essentially restricted to lymphatic endothelia, with expression in subsets of pancreatic and gastrointestinal epithelia. However, it was also detected in embryonic liver and heart. Prox1 was consistently expressed in lymphangiomas, venous hemangiomas, Kaposi sarcoma, and endothelia of spindle cell hemangioma, kaposiform hemangioendothelioma, and retiform hemangioendothelioma and half of epithelioid hemangioendotheliomas. It was present in most cutaneous angiosarcomas from different sites, but was less commonly expressed in deep soft tissue and visceral angiosarcomas. In contrast, Prox1 was generally absent in capillary and cavernous hemangiomas. In positive hemangiomas and angiosarcomas it was coexpressed with podoplanin, another marker of lymphatic endothelial phenotype. There was an inverse correlation with CD34 expression. The expression in mesenchymal non-endothelial neoplasm was limited. Prox1 was detected in 5/27 synovial sarcomas, specifically in the epithelia of biphasic tumors. 4/16 Ewing sarcomas and 5/15 paragangliomas were also positive. All melanomas and undifferentiated sarcomas were negative. Among epithelial neoplasms, Prox1 was detected in 18/38 colonic carcinomas and 10/15 cholangiocarcinomas, and in a minority of pulmonary, prostatic, and endometrial adenocarcinomas. The common Prox1 expression in angiosarcoma and its rare presence in non-vascular mesenchymal tumors make this marker suitable in the diagnosis of angiosarcoma and Kaposi sarcoma. However, presence of Prox1 in some malignant epithelial tumors necessitates caution in applying Prox1 as a marker for vascular tumors. Common Prox1-expression in angiosarcoma may reflect lymphatic endothelial phenotype in these tumors. Its patterns of expression in hemangiomas and angiosarcoma may be diagnostically useful and offer a new parameter in biologic classification of vascular tumors.